2019
DOI: 10.1039/c9nj04426d
|View full text |Cite
|
Sign up to set email alerts
|

An efficient ruthenium(ii) tris(bipyridyl)-based chemosensor for the specific detection of cysteine and its luminescence imaging in living zebrafish

Abstract: A water-soluble, red emissive and cysteine-specific probe has been achieved through 1,4-addition of cysteine to α,β-unsaturated ketones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Notably, the bioapplication of PM has been addressed by examining the practicability for Hg 2+ sensing in reduced newborn-calf serum. 87,88 As shown in Fig. 7B, upon the addition of varying amounts of reduced serum (5, 10, 20, 30, 40, 50, 60 mL) to the solution of PM-Hg 2+ , the relative emission intensity remains basically unchanged, which demonstrates the high efficiency of the Hg 2+ -promoted hydrolysis of PM in reduced serum.…”
Section: Practical Application Studiesmentioning
confidence: 82%
“…Notably, the bioapplication of PM has been addressed by examining the practicability for Hg 2+ sensing in reduced newborn-calf serum. 87,88 As shown in Fig. 7B, upon the addition of varying amounts of reduced serum (5, 10, 20, 30, 40, 50, 60 mL) to the solution of PM-Hg 2+ , the relative emission intensity remains basically unchanged, which demonstrates the high efficiency of the Hg 2+ -promoted hydrolysis of PM in reduced serum.…”
Section: Practical Application Studiesmentioning
confidence: 82%
“…Recent studies have also revealed that the concentration of biothiols is implicated in different conditions, such as inflammation, cardiovascular diseases, HIV infection and cancers [ 161 ]. To detect biothiols in the body, a series of Ru(II) complex chemosensors have been developed through the following response mechanisms, (1) nucleophilic substitution and cleavage of the sulfonamide or sulfonate ester bond [ 212 214 ], (2) cyclization of aldehyde group with amino and thiol groups [ 100 , 215 , 216 ] and (3) others [ 217 ], such as reaction with azo group [ 218 ] and α,β-unsaturated ketone [ 219 ], cleavage of NBD and displacement of metal ions [ 139 , 220 ].…”
Section: Ru(ii) Complex Chemosensors For Amino Acidsmentioning
confidence: 99%
“…Interestingly, functionalization of [Ru(bpy) 3 ] 2+ with two α,β‐ unsaturated ketone moieties gives complex 84 that can discriminate Cys from Hcy and GSH in live cells and zebrafish [97] . The complex exhibits 30‐fold emission enhancement upon incubation with Cys for 10 min, while treatment of the complex with Hcy and GSH does not give similar photophysical changes.…”
Section: Luminescent Transition Metal Complexes As Activity‐based Pro...mentioning
confidence: 99%